Effects of diffuse effluents from Botshabelo on the microbiological quality of water in the Modder River - Jagals, Paul (Bloemfontein: Central University of Technology, Free State, 1994)
The value of selected indicator micro-organisms for assessment of faecal pollution of water, as well as the distinction of faecal pollution of animal or human origin of pollution, has been investigated. The following indicators were included: faecal coliform bacteria, faecal streptococci, sorbitol-fermenting bifidobacteria, Rhodococcus coprophilus, somatic and male-specific coliphages and phages of Bacteroides tragilis. Comparative tests were carried out on water samples collected from a stream and river, and their respective catchments, exposed to predominantly faecal pollution of domestic animal origin. The same stream and river with catchments, were sampled after downstream exposure to run-off from a low socioeconomic developing settlement with restricted sanitation. Samples were collected from perennial flow in the stream and river during the dry season and from storm water run-off during general rain and immediately after thunder storms. Storm water run-off reached faecal coliform counts of up to 4 400 000 per . 100 ml, which is equivalent to that of many sewage effluents. Faecal pollution of the aquatic environment was less during the dry season. Sorbitol-fermenting bifidobacteria were identifiable with faecal pollution of human origin, and R coprophi/us with that of animal origin. Male specific coliphages were identifiable with sewage pollution as well as general faecal pollution of water. Certain selected ratios for the indicator organisms indicated possible distinction between faecal pollution of human origin and faecal pollution predominantly of animal origin under certain circumstances. Phages of B tragi/is were not detected in any of the samples, which implies that their application in this situation would require more sensitive techniques. The results show that the run-off from the developing settlement constituted a major source of pollution for a river catchment which downstream is used as a source of water for human consumption and that faecal pollution of human and animal origin can reliably be distinguished by means of combinations of appropriate indicators.
Thesis
Keywords: Water quality - South Africa - Modder River; Modder River (South Africa) - Quality control; Water - Pollution - South Africa - Modder River; Diffuse effluents; water quality indicators; human pollution; pathogens